Answer: options A) x = -1 and C) x = 1Step-by-step explanation:The graph show that the two functions intersect at x = - 1 and x = 1, so those are the solutions to the equality given. That is the options A) and C).
Note that the first function,
![f(x)=- (3)/(4) x+2 (1)/(4) = - (3)/(4) x+ (9)/(4)](https://img.qammunity.org/2019/formulas/mathematics/college/xg35tvbz9iogt5j8zbf9d5jcuhexvidu2a.png)
is the the straight line.
The function g(x) is
![( (1)/(2)) ^x+1](https://img.qammunity.org/2019/formulas/mathematics/college/n2yng6m1thiybtdtb3pxyrx4hvkf6g1igy.png)
When you replace the value of x = -1 you get:
f(-1) = - (3/4) (-1) + 9/4 = 3/4 + 9/4 = 12 / 4 = 3
g(-1) = (1/2)^(-1) + 1 = 2 + 1 = 3
So, f(-1) = g(-1).
When you replace x = 1 you get:
f(1) = -(3/4)(1) + 9/4 = -3/4 + 9/4 = 6/4 = 3/2
g(1) = (1/2)^1 + 1 = 1/2 + 1 = 3/2
So, f(1) = g(1).
And in that way you have shown analiticaly that x = -1 and x = 1 are both solutions of f(x) = g(x).